Diode-pumped, actively Q-switched Nd,La:CaNb2O6 self-Raman laser at 1,174 nm - Zhuang, Youyi; Mao, Wenjie; Gong, Xinghong; Jin, Xinxin; Li, Zhihong; Huang, Yidong; Duan, Yanmin (Frontiers in Physics, 2022)
Diode end-pumped Nd,La:CaNb2O6 self-Raman laser with acousto-optic Q-switching was successfully demonstrated for the first-Stokes wave at 1174 nm generation. A 1 at.% Nd3+ and 1 at.% La3+ doped CaNb2O6 crystal in dimensions 3×3×14.3 mm3 was used as the self-Raman laser crystal. Doping 1 at.% La3+ ions into this crystal could subdue the fluorescence quenching caused by cross relaxation between Nd3+ ions, and finally improve the laser output performance. Under the incident pump power of 9.9 W, the first-Stokes wave at 1174 nm with the maximum output power up to 928 mW was obtained, with the diode to Stokes conversion efficiency of about 9.4 %. The results show that the Nd,La:CaNb2O6 is also an promise self-Raman crystal for efficient fundamental and Raman laser operation.